Local Business Cycles and Local Liquidity - Bernile, Gennaro; Korniotis, George; Kumar, Alok; Wang, Qin (Journal of Financial and Quantitative Analysis, 2015)
Abstract This study examines whether state-level economic conditions affect the liquidity of local firms. We find that liquidity levels of local stocks are higher (lower) when the local economy has performed well (poorly). This relation is stronger when local financing constraints are more binding, the local information environment is more opaque, and local institutional ownership levels and trading intensity are higher. Overall the evidence supports the notion that the geographical segmentation of U.S. capital markets generates predictable patterns in local liquidity.